Determination of the Potassium Content in Fruit Samples by Gamma Spectrometry to Emphasize its Health Implications - Saleh, Dedawan S.; Ahmad, Saddon T.; Kareem, Sarmad R. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2022)
In this study, the activity concentration of 40K and its’ concentrations in 24 different types of fruits were determined using high purity germanium (HPGe) and sodium iodide scintillation (NaI) detectors. The results of the two measurements are consistent. The Maximum and minimum activities of 40K in dry samples were 750.61 ± 11.88 and 15.64 ± 0.86 Bq kg−1 in apricot and olive, respectively, while in fresh samples they were 152.27 ± 2.12 and 1.99 ± 0.11 Bq kg−1 in dates and olive, respectively. The highest and lowest potassium contents were 489.81 and 6.42 mg/100gm in fresh dates and olives, respectively. Drupe and Tropical fruits, as a fruit family, typically had the highest level of 40K activity and potassium concentration, whereas pome fruits showed the lowest levels. Many of these commonly consumed fresh fruits with rich potassium and water contents are lowering hypertension and improving the hydration status (HS) in people’s nutrition. The rate of potassium-40 and total potassium concentration intake for a single unit or portion of the fruits was calculated.